Travel as a Catalyst for Transformation in Yann Martel’s Life of Pi - Thapa, Hukum (Humanities and Social Sciences Journal, 2024)
This paper scrutinizes travel as a catalyst for transformation in Yann Martel's philosophical and adventurous novel, Life of Pi. It analyzes how travel influences Pi’s personal, psychological, and spiritual development, acting as a catalyst for his transformation and maturation. The study asserts that travel serves as a rite of passage that transforms Pi’s belief systems, fortifies his faith, and enhances his comprehension of identity and existence. Based on a qualitative research methodology, this study draws upon Carl Jung’s theory of psychological transformation and archetypes, Joseph Campbell’s framework of the hero’s journey, and Victor Turner’s concepts of rites of passage and liminality to analyze Pi’s voyage from India to Canada as a complex process of psychological, spiritual, and existential self-discovery. Ultimately, it concludes that travel enhances Pi’s maturity, sensibility, and sense of duty, allowing him to grasp the intricacies of the universe and humanity. This study also opens pathways for further interdisciplinary research through cultural, postcolonial, ecocritical, and young adult perspectives on travel.